2015
DOI: 10.1016/j.jmps.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Collective behaviour and spacing of necks in ductile plates subjected to dynamic biaxial loading

Abstract: Diffuse or localized dynamic necking of a sheet metal is a major issue in high speed forming processes, leading to unacceptable thinning and even failure if fully developed, and in the dynamic behaviour of metallic structural elements of small thickness used for energy absorption purposes. This process is frequently related to the collective development of localization bands resulting in a necking pattern which depends on the sheet properties and on the loading conditions. This work investigates the spacing be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 75 publications
3
40
0
Order By: Relevance
“…In this section we aim at uncovering the role played by the initial conditions, the boundary conditions and the sample slenderness on the formation of multiple localization patterns. The way in which these factors either favour or preclude the emergence of multiple necking bands has been hardly investigated in the literature [73], thus we intend to give some indications about it here. Fig.…”
Section: Multiple Localization Patternmentioning
confidence: 99%
“…In this section we aim at uncovering the role played by the initial conditions, the boundary conditions and the sample slenderness on the formation of multiple localization patterns. The way in which these factors either favour or preclude the emergence of multiple necking bands has been hardly investigated in the literature [73], thus we intend to give some indications about it here. Fig.…”
Section: Multiple Localization Patternmentioning
confidence: 99%
“…On the other hand, while the same rationale has been employed by other authors, e.g. Zaera et al [52] and N'souglo et al [35], we are aware that it is also customary in the literature to impose the stretch rate as the loading condition [49,34], since it may bear closer resemblance to the actual boundary conditions in dynamic experiments like the expansion of hemispherical shells (see Mercier et al [30]). Hence, stability analysis results and finite element calculations obtained imposing the stretching rate, namelyε 0 xx = 4000 s −1 andε 0 xx = 80000 s −1 , are reported in Appendix A.…”
Section: Remarkmentioning
confidence: 84%
“…Furthermore, we think that the overall trends and conclusions obtained in this paper are still valid for actual materials with flow stress dependent on strain, strain rate and temperature. On other hand, previous works reported in the literature suggested that strain hardening delays necking formation [20], the strain rate hardening increases the necking strain and the average spacing between necks [21], and the thermal softening promotes early formation of necks and leads to the decrease of the distance between consecutive necks [46]. Nevertheless, determining to which amount strain, strain rate and temperature affect the necking pattern at high strain rates, when inertia effects are important, still requires further research.…”
Section: Finite Element Modelmentioning
confidence: 95%